Humanized mouse models of immunological diseases and precision medicine - Shultz, Leonard D.; Keck, James; Burzenski, Lisa; Jangalwe, Sonal; Vaidya, Shantashri; Greiner, Dale L.; Brehm, Michael A. (Mammalian genome, 2019)
With the increase in knowledge resulting from the sequencing of the human genome, the genetic basis for the underlying differences in individuals, their diseases, and how they respond to therapies is starting to be understood. This has formed the foundation for the era of precision medicine in many human diseases that is beginning to be implemented in the clinic, particularly in cancer. However, preclinical testing of therapeutic approaches based on individual biology will need to be validated in animal models prior to translation into patients. Although animal models, particularly murine models, have provided significant information on the basic biology underlying immune responses in various diseases and the response to therapy, murine and human immune systems differ markedly. These fundamental differences may be the underlying reason why many of the positive therapeutic responses observed in mice have not translated directly into the clinic. There is a critical need for preclinical animal models in which human immune responses can be investigated. For this, many investigators are using humanized mice, i.e., immunodeficient mice engrafted with functional human cells, tissues, and immune systems. We will briefly review the history of humanized mice, the remaining limitations, approaches to overcome them and how humanized mouse models are being used as a preclinical bridge in precision medicine for evaluation of human therapies prior to their implementation in the clinic.